Interventions for Parental Anxiety in Preparation for Pediatric Surgery: A Narrative Review - Pooja Santapuram; Amanda L. Stone; Rachel Lane Walden; Louise Alexander (MDPI AG, 2021)
The preoperative experience can cause significant anxiety for both pediatric patients and their parents in the lead up to a surgical procedure. Pediatric anxiety in a preoperative setting has been shown to have significant negative downstream effects on the clinical outcomes of children and the healthcare system as a whole. Studies have found that preoperative parental anxiety has significant negative effects on children, regarding anxiety and emotional response. Therefore, interventions for parental preoperative anxiety are important to reduce the child's anxiety. This review provides a brief overview of a broad range of strategies used to alleviate parental anxiety in a preoperative setting. Preoperative education, play-based interventions, music therapy, the presence of parents at induction of anesthesia, and integrative preoperative preparation programs have all demonstrated some evidence for reducing parental preoperative anxiety. The ultimate goal of using interventions for parental preoperative anxiety is to equip healthcare systems to better support families and optimize the perioperative outcomes of children.